“Own Goodness and Service for Others” A Motivation to Serve People with Mental Disorders: Systematic Review - Flavianus Riantiarno; Lilik Zuhriyah; Heni Dwi Windarwati (GoAcademica Research & Publishing, 2020)
Volunteers have an important role in mental health services. Volunteers are present among the stigma and discrimination against people with mental disorders. To understand the motivation of volunteers in caring for people with mental disorders. A systematic review was conducted by collecting the results of scientific publications. The data bases used were ProQuest, PubMed, Sincedirect, and Springer link. Searching was carried out using the keywords of motivation, volunteers and mental disorders. Determination of the number of articles and articles contained in the review was determined by using PRISMA methods. Eight articles were found using the inclusion criteria for the article. Volunteer’s motivation was for their own goodness and service for others. Motivation of own goodness was divided into personal growth, altruism and self-existence. Motivation to serve others was to help others and contribute to society. There was strong evidence that volunteers had good motivation in improving the health status of people with mental disorders.